Deciphering Limitations to Meet Highly Stable Bio‐Hybrid Light‐Emitting Diodes. (15th August 2019) - Fernández‐Luna, Verónica; Sánchez‐de Alcázar, Daniel; Fernández‐Blázquez, Juan P.; Cortajarena, Aitziber L.; Coto, Pedro B.; Costa, Rubén D.
Abstract: Color down‐converting filters with fluorescent proteins (FPs) embedded in a polymer matrix have led to new bio‐hybrid light‐emitting diodes (Bio‐HLEDs), featuring stabilities of 100 h and <1 min at low and high applied currents, respectively. Herein, the FP deactivation mechanism in Bio‐HLEDs at high driving currents is deciphered. Primarily, the nonradiative energy relaxation of FPs upon excitation promotes the release of excess energy to the polymer matrix, reaching 60 °C and, in turn, a significant thermal emission quenching. This is circumvented by changing the device architecture, achieving stabilities of >300 h at high driving currents. Here, the photoinduced deactivation mechanism takes place, consisting of a slow and reversible partial dehydration followed by a quick and irreversible deactivation of the highly emissive ionic form. This is supported by steady‐state/time‐resolved emission, circular dichroism, and electrochemical impedance spectroscopic techniques. Overall, the limitations of Bio‐HLEDs concerning matrix, buffers, device design, and FP stability are highlighted as key aspects to achieve efficient and stable devices. Abstract : The first steps toward the optimization of bio‐hybrid light‐emitting diodes are presented. Using a remote architecture, the thermal quenching of fluorescent proteins (FPs) upon excitation is circumvented. This increases the device stability from a few minutes to hundreds of hours. The FP deactivation is rationalized using spectroscopic assays to obtain valuable insight about the FP structural modifications under device operating conditions.